2023
DOI: 10.1037/neu0000886
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the hypothesis of language retrogenesis from an evolutionary perspective.

Abstract: Objective: In this article, we reexamine the hypothesis of language retrogenesis, that is, the assumption that language change over healthy ageing mirrors, albeit inversely, language acquisition by the child. We additionally question whether this inverse pattern can as well be observed at the cognitive and neurobiological levels, and whether it can be informative (and a consequence, in fact) of how language evolved in humans. Method: We compare the language strengths and weaknesses signifying language acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 193 publications
(288 reference statements)
0
2
0
Order By: Relevance
“…Using eight neuropsychological tests, we measured the LP performance, domain-general (DG), and language-specific processes (see Table 1). We also considered education levels as previous work suggested that this factor modulates semantic retrieval 22 . Education attainment was mapped to a 10-point scale ranging from CSE/GCSE diploma to PhD.…”
Section: Cognitive Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Using eight neuropsychological tests, we measured the LP performance, domain-general (DG), and language-specific processes (see Table 1). We also considered education levels as previous work suggested that this factor modulates semantic retrieval 22 . Education attainment was mapped to a 10-point scale ranging from CSE/GCSE diploma to PhD.…”
Section: Cognitive Datamentioning
confidence: 99%
“…In this context, longer naming latencies and more frequent tip-of-the-tongue situations with age could be mitigated by enhanced semantic access thanks to a distributed anatomo-functional reorganization 12,[18][19][20] . Specifically, the enrichment of semantic repositories 2,21 could represent a strategy for maintaining the retrieval of words with stronger semantic connections 22 and conceptual categorization 23,24 contingent upon accumulated vocabulary knowledge throughout adulthood 25,26 . However, more pronounced inhibition deficits could challenge the ability to ignore task-irrelevant information [27][28][29] , leading to longer searches through a growing semantic store.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this semantic expertise (Spreng & Turner, 2019) contributes to preserving language comprehension and implementing compensatory mechanisms to mitigate LP decline in older adults (Baciu et al, 2021). At the behavioral level, while advanced age is associated with the most significant LP decline (e.g., lower naming accuracy) (Shafto & Tyler, 2014; Verhaegen & Poncelet, 2013), increased naming latencies in low-frequency words with poorer semantic connections may onset in middle age (Benítez-Burraco & Ivanova, 2023). Therefore, a comprehensive investigation of midlife is crucial to understanding the aging mechanisms at play and predicting the neurocognitive trajectory in older late adulthood (Lachman, 2015; Park & Festini, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This means that language changes during ageing can serve as proxies for the cognitive strengths and weaknesses of the elderly as they age. Interestingly, the most complex aspects of language (like embedding, as usually found in dependent clauses) are impacted earlier by ageing, pretty much as they emerge later in the child, and they depend on brain circuits that are early‐demyelinated during ageing, pretty much as they are late‐myelinated during childhood (Benítez‐Burraco & Ivanova, 2023). This is seemingly due to their phylogenetic novelty, which results in less robust mechanisms of resistance to ontogenetic damage.…”
Section: Introductionmentioning
confidence: 99%